A Personal Note on Open Access in Linguistics - Müller, Stefan (Journal of Language Modelling, 2012)
This paper contains only known facts about open access, but they are put into a rather personal perspective that may help others to understand the importance of Open Access in science in general and in linguistics in particular. This paper tries to motivate Open Access publishing, with a particular focus on publishing books. In Section 1, I describe the problems in accessing relevant information in economically weak countries, the problem of underpayment in the humanities, and usage restrictions of traditionally published books. Section 2 explains the factors that contribute to book prices. Section 3 briefly describes Open Access publishing and print on demand services. In Section 4, I address some challenges for Open Access publishing and suggest ways to ensure quality control, proper typesetting, and efficient marketing. Section 5 discusses Open Access approaches of profitorientated publishers. Section 6 deals with Open Access and getting tenure and promotion, and Section 7 is about radical opinions about copyrights outside of academia. Version of 7th January 2012 (minor editorial changes).